The Identity Registration System, Identification Number and National ID Card During the Vichy Regime (France, 1940-1944) - Pierre Piazza (Criminocorpus)
The « Carte d’identité de Français » (ID card for French citizens) was enacted in France starting in October 1940. This paper examines the cooperation between the statistical service of the French finance ministry and the French interior ministry in order to implement the card during German occupation. Each of these actors cooperated for reasons that are analyzed in detail. The intervention of the statistical service in the delivery process of the new document for the identification of nationals occasionally hampered some repressive law enforcement objectives. However, other statistical service initiatives fully embraced the logic of the Vichy regime’s most sinister motives.